Necrotizing ulcerative gingivitis - Rayhana Malek; Amina Gharibi; Nadia Khlil; Jamila Kissa (Wolters Kluwer Medknow Publications, 2017)
Necrotizing ulcerative gingivitis (NUG) is a typical form of periodontal diseases. It has an acute clinical presentation with the distinctive characteristics of rapid onset of interdental gingival necrosis, gingival pain, bleeding, and halitosis. Systemic symptoms such as lymphadenopathy and malaise could be also found. There are various predisposing factors such as stress, nutritional deficiencies, and immune system dysfunctions, especially, HIV infection that seems to play a major role in the pathogenesis of NUG. The treatment of NUG is organized in successive stages: first, the treatment of the acute phase that should be provided immediately to stop disease progression and to control patient's feeling of discomfort and pain; second, the treatment of the preexisting condition such as chronic gingivitis; then, the surgical correction of the disease sequelae like craters. Moreover, finally, maintenance phase that allows stable outcomes. This case report describes the diagnosis approach and the conservative management with a good outcome of NUG in a 21-year-old male patient with no systemic disease and probable mechanism of pathogenesis of two predisposing factors involved.